2005
DOI: 10.1143/jjap.44.7433
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical Properties of InGaN for H2 Generation from Aqueous Water

Abstract: The photoelectrochemical properties of In x Ga1-x N (x=0.02 and 0.09) were compared with those of GaN. The band-edge potentials of In x Ga1-x N were determined by the Mott–Schottky plot for the first time. The gas generation from a counterelectrode using the In0.02Ga0.91N working electrode was the highest of the three samples. Band-edge potentials and the light absorption of a working photoelectrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 11 publications
1
59
0
Order By: Relevance
“…Furthermore, alloys of InN and GaN have recently attracted interest for use in multijunction photovoltaic devices [10][11][12] and as photoelectrodes for water splitting. [13][14][15][16][17][18][19][20] In photochemical water splitting, the InGaN semiconductor absorbs sunlight and thereby produces electrons and holes, which drives the water-splitting reaction. Successful photoelectrode materials must fulfill at least the following three criteria: (i) The band gap must be such that a significant fraction of the solar spectrum is absorbed; (ii) the conduction band (CB) and valence band (VB) must straddle the redox potential of hydrogen and water; and (iii) the material must be corrosion resistant.…”
Section: Alloys Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, alloys of InN and GaN have recently attracted interest for use in multijunction photovoltaic devices [10][11][12] and as photoelectrodes for water splitting. [13][14][15][16][17][18][19][20] In photochemical water splitting, the InGaN semiconductor absorbs sunlight and thereby produces electrons and holes, which drives the water-splitting reaction. Successful photoelectrode materials must fulfill at least the following three criteria: (i) The band gap must be such that a significant fraction of the solar spectrum is absorbed; (ii) the conduction band (CB) and valence band (VB) must straddle the redox potential of hydrogen and water; and (iii) the material must be corrosion resistant.…”
Section: Alloys Ofmentioning
confidence: 99%
“…InGaN alloys have been found to fulfill these criteria and are, therefore, a potential candidate as a photoelectrode. [13][14][15][16][17][18][19][20] In the present study we focus on criteria (i) and (ii) and the materials properties of interest are, therefore, the band gap and band alignments.…”
Section: Alloys Ofmentioning
confidence: 99%
“…Experimentally, single crystalline In x Ga 1-x N nanowires with compositions up to x = 0.4~0.5 have been realized. 16 Although the InGaN alloy is a very promising water splitting material, only a few studies have been reported [17][18][19] with no studies on nanowire geometries.One dimensional nanostructures have been demonstrated to be efficient in photoelectrochemical (PEC) cell and photovoltaic cell applications because they can decouple the directions of light absorption and charge carrier collection. [20][21] When the life time of the minority carrier is short, the minority carrier can recombine in bulk before it reaches the semiconductor/electrolyte junction.…”
mentioning
confidence: 99%
“…Being strongly 11,12 properties of the semiconductor surface are closely related and dependent on the indium content, the CB edge lies below influence the performance of the whole device. The role of the surface states on the charge transfer across the semiconductor− liquid interface (SLI) is of great importance, especially on how they can severely limit the photocarrier extraction, leading to an undesired overpotential.…”
Section: Introductionmentioning
confidence: 99%